Pursuing Public Trust: Tax Reform Communication during the Indonesian Government Transition - Neni Puji Artanti; Akhmad Muwafik Saleh; Bambang Dwi Prasetyo (Universitas Darussalam Gontor, 2025)
The credibility of tax policy is relies not only on excellent policy design but also effective communicated to the public. Tax policy significantly affect the public interest, so the Directorate General of Taxation's (DGT) communication strategy is critical for sustaining public trust. During Indonesia’s 2024 political transition, the DGT faced challenges in communicating sensitive tax reform issues, including the adjustment of Value-Added Tax rate and the implementation of the Coretax system. This qualitative case study applies the Contingency Theory of Accommodation to examine how predisposing and situational factors shaped the communication stance along the advocacy–accommodation continuum. The research triangulated in-depth interviews with public relations managers and social media specialists, document analysis, and qualitative content analysis of 74 social media posts and 284 news articles from October 2024 to January 2025. The findings reveal that although the Directorate General of Taxation implements the “communication as part of policy” paradigm reflecting its predisposed strategy, situational complications such as fragmented information bubbles, political residue, and the “lost period” of public preparation, dominated the communication dynamics during the transition A key theoretical contribution of the study is the identification of algorithm-driven fragmentation as situational pressures that constrained the effectiveness of predispositional orientations. The study also highlights the need to elevate the communication strategy to a higher regulatory level to ensure a robust communication process even during a transitional period.